Multilateral training : re-examining the concept’s practicality / Oleksandr Krasilshchikov - Oleksandr, Krasilshchikov (Faculty of Sports Science and Recreation, 2014)
Multilateral Training (MT) concept is going through its second resurfacing in the world of sports and even some of the top achievements, including some recent swimming world records are partially attributed to it. Researchers in many countries including Malaysia are intensively re-looking into the concept and into practical applications of multilateral training. It is not only being reconsidered in relation to early years of training, but also in an attempt to identify and recognise its role at the advanced stages of athletes’ training towards the top performance. Originating from the merger of two completely unrelated concepts, multilateral training grew through the years of fast progress in sports in the Eastern Europe and ditched almost into the oblivion when specialisation in sports has been recognised as critical for elite sports. Though admitting its role in sport training, most specialists consider MT as feature related only to the opening stages of the long term training. Few agree that certain degree of multilaterality should be still present during specialized training and almost none believes that there is a scope for multilateral training at the advanced stages of long term preparation in sports.